Case Report: Coronary-Pulmonary Fistula Closure by Percutaneous Approach: Learning From Mistakes - Rubimbura, Vladimir; Girod, Grégoire; Delabays, Alain; Meier, David; Rotzinger, David C.; Muller, Olivier; Qanadli, Salah D.; Eeckhout, Éric (Frontiers in Cardiovascular Medicine, 2022)
Coronary-pulmonary artery fistulas (CPAF) are congenital vascular anomalies detected incidentally in most cases. When a significant left-right shunt exists, surgical, or percutaneous treatment is indicated. We describe a challenging case of CPAF closure, by percutaneous approach, in a patient symptomatic for dyspnea and evidence of a significant left-right shunt. A first attempt to close the fistula was performed implanting a vascular plug but it quickly embolized. The plug was successfully retrieved. In a second attempt, we deployed several coils before implanting the vascular plug with total closure of the fistula. The combination of plugs and coils is associated with a higher success rate of closure.